(3egGQGJ GdEJUGd (B/s - (3GdScGQfI, HdGd Ndas ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2015)
(3jVe eaghe egGQGJ GdEJUGd h egGQGJ GdJYGed eY GdBNQjf, HfGA GdYdGbGJ aj GdHjFI GdLGeYjI, af GdJCKjQ HGdBNQjf EjLGHG, TNUjI GdQDSGA h af GdJYGed eYge, egGQGJ GdebGHdI, HfGA GdKbI aj GdfaS, egGQGJ GdEUZGA h GdJMOK, egGQGJ EOGQI GdhbJ, GdhYj GdPGJj, egGQGJ GdCfJQfJ, egGQGJ GdESJPcGQ(B.s
Keywords: (3GdEJUGds; (3GdYdGbGJ GdYGeIs; (3hSGFd GdEJUGd GdLeGgjQjs